Party politics and service delivery in the public sector: a case of the Ministry of Agriculture, mechanisation and Irrigation Development - Chiremba, Honest (Midlands State University, 2017)
Most governments in African societies are characterised by failure to address their electoral promises hence the degree of public service delivery is not all inclusive in the sense that it is mainly anchored on political affiliation while marginalising descending voices. It is against this background that this study seeks to assess the effects of party politics on public service delivery in the Ministry of Agriculture, Mechanisation and Irrigation Development. The agricultural sector is the backbone of the Zimbabwean livelihood and the greater part of the population across all ethnic and cultural backdrops are mostly directly or indirectly involved in it. This saw the government through the Ministry designing programmes and policies aimed at boosting the sector against a backdrop of harsh economic conditions and subsequent drought, an endeavour which has been captured by those in the political arena to strengthen their political grip through directing service delivery towards targeted groups loyal to the ruling party or as way of garnering new electoral support. The study made us of a descriptive research design in which various instruments were used to gather data in the form of Interviews, questionnaires and observations. Using descriptive statistics, the outcome of the research highlighted that programmes and policies in the Ministry of Agriculture aimed at revitalising the sector have been hijacked for political gains. In light of the findings the Ministry of Agriculture is advised to detach from actively involved in party politics and craft programmes that inclusively benefits the citizens regardless of political belief. The Government of Zimbabwe is also advised to set up independent commissions that oversees the allocations of service delivery.